(untitled) (Revista Internacional de Folkcomunicação, 2020)
The attributes of the ethnomusicological discipline and the need to relate to Brazilian ancestral music become clear, with the aim of socially valuing the different musical evidences of the original native peoples. Historically, ethnology was developed in Brazil, being the basis for the analysis of musical manifestations of various musical styles. The particularities of the science in question are appropriate in this article for the rescue and evaluative knowledge of ancestral peoples and their musicalities. Thus, we hope to collaborate with the characterization and identification of the musical cultural diversity and the cultural identity of our country. Cultural diversity; Musical Culture; Ancestrality; Identity; Ethnomusicology.